KERAGAAN HASIL ANALISIS PROKSIMAT BIJI KELOR (Moringa oleifera Lam.) PADA BERBAGAI TEKNIK PENGERINGAN BIJI - Bambang Budi Santoso; IGM Arya Parwata; Jayaputra Jayaputra (Fakultas Teknologi Pangan & Agroindustri (Fatepa) Universitas Mataram dan Perhimpunan Teknik Pertanian (PERTETA), 2019)
One of the advantages of Moringa is the proximate component of seeds, which can be seen as a source of further planting material and also as an industrial processed base material, whose quality is largely determined by how to process the seeds. This study aims to determine the performance of the proximate component of Moringa seeds in various ways of drying seeds. The drying technique are drying using an oven at 60 Â± 3 OC and at 105 Â± 3 OC, drying with sunlight, and drying with wind flow (dry wind). 250 g of seed samples were used in each drying technique with three replications. Proximate analysis of Moringa seeds was carried out using the standard method by AOAC (2000). The results showed that the drying technique had a significant effect on the proximate component of Moringa seeds due to differences in drying temperatures. There was a decrease in the fat and protein content of the seeds as drying temperatures increased, especially in oven drying techniques (60 OC and 100 OC). Wind drying techniques and sun drying were better techniques for drying Moringa seeds